Analysis of Career Variable to Organization Commitment in Jakarta's Banks - Supai Muhammad Noor (Business and Entrepreneurial Review, 2007)
The background of this research was the fact that many employees shifted from a company to other company to get better career, hence causing high employee turnover rate. Therefore. applying accurate career strategy can become determination of organizational commitment. The objectives of this research are to identify the effect of career planning, career development program, career strategy, career satisfaction to organizational commitment. The design of this research applies hypothesis testing to examine all hypotheses in this study. The methods used in this study were mulltiple regressions between independent variables and dependent variable. Data analysis used in this research was collected by distributing questionnaires which were distributed to 160 respondents in  Jakarta. There were 160 responses of which 150 were completed and usable to be analyzed using multiple regressions. This research concludesthat there was positive and significant effect between career planning, career development program, career strategy, and career satisfaction with organizational commitment.